2018
DOI: 10.1002/cpnc.70
|View full text |Cite
|
Sign up to set email alerts
|

Label‐Free Electrophoretic Mobility Shift Assay (EMSA) for Measuring Dissociation Constants of Protein‐RNA Complexes

Abstract: The electrophoretic mobility shift assay (EMSA) is a well‐established method to detect formation of complexes between proteins and nucleic acids and to determine, among other parameters, equilibrium constants for the interaction. Mixtures of protein and nucleic acid solutions of various ratios are analyzed via polyacrylamide gel electrophoresis (PAGE) under native conditions. In general, protein–nucleic acid complexes will migrate more slowly than the free nucleic acid. From the distributions of the nucleic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 42 publications
(49 reference statements)
2
25
0
Order By: Relevance
“…In addition, the size of a molecule is not an issue for the ITC assay, whereas the sensitivity of other biophysical techniques such as SPR and bio-layer interferometry (BLI) is largely dependent on the molecular weight of their analytes. ITC has been increasingly [65] used in determining protein-protein [66,67], protein-nucleic acid [68][69][70] and proteinsmall molecule interactions [71,72]. In recent years, ITC has also been applied in profiling the thermodynamic parameters and cooperativities of PROTAC molecules, providing invaluable insights into the interplay between a PROTAC molecule and its target protein and E3 ligase [25,29,34,73,74].…”
Section: Isothermal Titration Calorimetrymentioning
confidence: 99%
“…In addition, the size of a molecule is not an issue for the ITC assay, whereas the sensitivity of other biophysical techniques such as SPR and bio-layer interferometry (BLI) is largely dependent on the molecular weight of their analytes. ITC has been increasingly [65] used in determining protein-protein [66,67], protein-nucleic acid [68][69][70] and proteinsmall molecule interactions [71,72]. In recent years, ITC has also been applied in profiling the thermodynamic parameters and cooperativities of PROTAC molecules, providing invaluable insights into the interplay between a PROTAC molecule and its target protein and E3 ligase [25,29,34,73,74].…”
Section: Isothermal Titration Calorimetrymentioning
confidence: 99%
“…Identification of nucleic acid-binding proteins is one of the most important tasks in molecular biology. Currently, nucleic acid-binding proteins can be identified and further characterized by several experimental techniques, including pull-down assays [ 2 , 3 ], yeast one-hybrid system [ 4 , 5 ], electrophoretic mobility shift assays [ 6 , 7 ], chromatin immunoprecipitation [ 8 , 9 ], and by other specialized techniques [ 10 , 11 ]. However, it is time-consuming and expensive to identify nucleic acid-binding proteins by experimental approaches [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on HDL titrations, the binding affinity of HDL to tDR-GlyGCC-30-AF546 was calculated ( Fig. S2B ), as previously described [32], and results from EMSA confirmed that HDL harbors strong affinity towards tDR-GlyGCC-30. These results support that HDL preferentially bind to ssRNAs and possess strong affinity to tDRs based on length and sequence.…”
Section: Resultsmentioning
confidence: 75%
“…EMSA were performed as previously described [32]. Briefly, AF546-tDR-GlyGCC-30 (1µM) was incubated with HDL (serial dilutions) and crosslinked (UV 254nm) for 15min on ice.…”
Section: Electrophoretic Mobility Shift Assays (Emsa)mentioning
confidence: 99%